Anti-Monopoly Compliance System: New Law, New System - Doniyor Abduazizov (Genius Journals, 2023)
Indeed, the new "Competition Law" includes various new institutions, and the main topic of this article is the analysis of the antimonopoly compliance system. Antimonopoly compliance is a new legal system in competition policy, according to Article 9 of the Law 2023 "On Competition" the system encourages "to ensure the compliance of activity with the legislation on competition, to identify the risk of violations and to prevent them a system of internal organizational measures and measures aimed at". The basis of this system is the Decree No. 6019 of July 6, 2020 of the President of the Republic of Uzbekistan "On additional measures to further develop the competitive environment and reduce state participation in the economy" and the Resolution of the Cabinet of Ministers "On measures to introduce the anti-monopoly compliance system” was developed in accordance with the decision No. 114 dated March 2, 2021.
Keywords: competition law; anti-monopoly compliance; authorized person